Use of an expenditure reducing model in railway carriage - Lingaitiene, Olga; Lingaitis, Vytautas (Transport, 2006)
Passenger transportation by railway is fast, safe, convenient and affordable for people, but it is usually not profitable for the state. Therefore, making passenger transportation profitable is a task of vital importance. Various calculations are used to optimize this process. The paper considers the problems of economical passenger transportation which may by described by two models: the first model is based on the assessment of income‐expenses of separate services, while the second model is related to the assessment of expenses according to their types. First Published Online: 27 Oct 2010